Characterizing nutrient uptake kinetics for efficient crop production during Solanum lycopersicum var. cerasiforme Alef. growth in a closed indoor hydroponic system - Lee, Ju Yeon; Rahman, Arifur; Azam, Hossain; Kim, Hyung Seok; Kwon, Man Jae (PUBLIC LIBRARY SCIENCE, 2017)
A balanced nutrient supply is essential for the healthy growth of plants in hydroponic systems. However, the commonly used electrical conductivity (EC)-based nutrient control for plant cultivation can provide amounts of nutrients that are excessive or inadequate for proper plant growth. In this study, we investigated the kinetics of major and minor nutrient uptake in a nutrient solution during the growth of tomato (Solanum lycopersicum var. cerasiforme Alef.) in a closed hydroponic system. The concentrations of major and minor ions in the nutrient solution were determined by various analytical methods including inductively coupled plasma-optical emission spectroscopy (ICP-OES), ion chromatography (IC), ion specific electrodes, and/or colorimetric methods. The concentrations of the individual nutrient ions were compared with changes in the EC. The EC of the nutrient solution varied according to the different growth stages of tomato plants. Variation in the concentrations of NO3-, SO42-, Mg2+, Ca2+, and K+ was similar to the EC variation. However, in the cases of PO43-, Na+, Cl-, dissolved Fe and Mn, Cu2+, and Zn2+, variation did not correspond with that of EC. These ions were generally depleted (to 0 mg L-1) during tomato growth, suggesting that these specific ions should be monitored individually and their supply increased. Nutrient uptake rates of major ions increased gradually at different growth stages until harvest (from < 3 mg L-1 d(-1) to > 15 mg L-1 d(-1)). Saturation indices determined by MINEQL+ simulation and a mineral precipitation experiment demonstrated the potential for amorphous calcium phosphate precipitation, which may facilitate the abiotic adsorptive removal of dissolved Fe, dissolved Mn, Cu2+, and Zn2+.
Keywords: FRUIT-QUALITY; TOMATO PLANTS; YIELD; PHOSPHATE; COPPER